Kaayanda musical arts for the installation of Shangwe chiefs : an epistemological, gendered, symbolic, interpretive, community-state model of sustaining tangible and intangible heritage in Zimbabwe - Nzewi, Meki (University of Pretoria, 2019)
Thesis (DMus)--University of Pretoria, 2019.